Jean Prouvé - Olio di macchina in libreria - Collotti, Francesco (Firenze Architettura, 2017)
Once the rubble of World War II was finally cleared away, a new apparently happy era began, marked by mass motorization. A passage was made from the society of needs to the consumer society. Jean Prouvé serially produces petrol stations with modular panels, in which he elegantly designs the shelving units in refined folded metal sheets, the pillars in brick colour, and the shelves in white.